2022
DOI: 10.1371/journal.pone.0275961
|View full text |Cite
|
Sign up to set email alerts
|

Current distribution of distributed all-polar cochlear implant stimulation mode measured in-situ

Abstract: Oticon Medical cochlear implants use a stimulation mode called Distributed All-Polar (DAP) that connects all non-stimulating available intracochlear electrodes and an extracochlear reference electrode. It results in a complex distribution of current that is yet undescribed. The present study aims at providing a first characterization of this current distribution. A Neuro Zti was modified to allow the measurement of current returning to each electrode during a DAP stimulation and was implanted in an ex-vivo hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 38 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…The derived eABR IS was based on recordings from stimulation on single electrodes, therefore neural channel interaction was not present in the corresponding results. In line with earlier studies, e.g., [ 32 , 33 , 34 ], eABR wave V amplitudes to increasing stimulation intensity on the middle electrode increased, hence the wave V amplitude in IS also increased. Regarding the latency of wave V, previous studies have reported both an increase [ 35 ] and decrease [ 36 ] with increasing the stimulus pulse duration.…”
Section: Discussionsupporting
confidence: 92%
“…The derived eABR IS was based on recordings from stimulation on single electrodes, therefore neural channel interaction was not present in the corresponding results. In line with earlier studies, e.g., [ 32 , 33 , 34 ], eABR wave V amplitudes to increasing stimulation intensity on the middle electrode increased, hence the wave V amplitude in IS also increased. Regarding the latency of wave V, previous studies have reported both an increase [ 35 ] and decrease [ 36 ] with increasing the stimulus pulse duration.…”
Section: Discussionsupporting
confidence: 92%
“…Note: We improved the software between S1 and S2 to allow current coding. 2 Distributed-all-polar (DAP) [7] indicates that current returns via the case electrode, like MP (monopolar) grounding, and simultaneously to all non-stimulating intra-cochlear electrodes, sometimes called 'common ground' (CG) (Figure 1).…”
Section: Stimulimentioning
confidence: 99%
“…Subject S2 used d coding for stimuli B−/B+ (current = 0.4 mA) and current coding for stimuli A+/A− (duration Note: We improved the software between S1 and S2 to allow current coding. 2 Distributed-(DAP) [7] indicates that current returns via the case electrode, like MP (monopolar) ground simultaneously to all non-stimulating intra-cochlear electrodes, sometimes called 'common (CG) (Figure 1). In each trial, we gradually increased the stimulation charge (i.e., pulse duration or amplitude) until either (1) the sound was too loud or (2) non-auditory sensations became too intense for the subject.…”
Section: Stimulimentioning
confidence: 99%
See 2 more Smart Citations